2022
DOI: 10.1002/nur.22290
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted rehabilitation training improves knee function and daily activity ability in older adults following total knee arthroplasty

Abstract: To evaluate the effects of robot‐assisted rehabilitation training on knee function and the daily activity ability of older adults following total knee arthroplasty (TKA). Eighty‐eight patients who underwent TKA were randomly assigned to a robot‐assisted rehabilitation or traditional therapy group. The patients in the control group were treated with traditional manual rehabilitation therapy, while the patients in the experimental group were subjected to the robot‐assisted rehabilitation program. Range of motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…[23] Several studies have shown that RAR improves knee ROM post-TKA. [12,13,24] The study results also support the finding that RAR produces this clinical benefit, as this study showed that both AROM and PROM improved through activeassistive joint support. In this study, RAR improved both AROM and PROM.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…[23] Several studies have shown that RAR improves knee ROM post-TKA. [12,13,24] The study results also support the finding that RAR produces this clinical benefit, as this study showed that both AROM and PROM improved through activeassistive joint support. In this study, RAR improved both AROM and PROM.…”
Section: Discussionsupporting
confidence: 81%
“…Cai and Mrotzek [9,13] reported the hospital stay of patients who used exoskeletons. This meta-analysis showed that patients who used exoskeletons experienced a significantly shorter hospital stay than the control group patients (SMD: −3.19, 95% CI: −4 to −2.38, P < .00001, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations